Mahram Menikahi Wanita Yang Punya Iddah - Jauhari, Jauhari (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
According to marriage legislation, marriage is a spiritual and physical bond between a man and a woman to form a happy and everlasting household based on the belief in the Almighty God. The prospective brides and grooms, however, do not pay attention to the circumstances or status of their respective partners. As a result, marriages are often canceled because one of the prospective spouses is still in a relationship with someone else or is in a waiting period or iddah. The research results show that if marriages that still have relationships or bonds as partners during the iddah period are prohibited, it is expected that there will no longer be polygamous marriages, especially for polyandrous women.